Safety culture & performance measurement in an oil and gas organization / Chow Cai Wing - Chow, Cai Wing (2018)
Most of the oil major companies in Malaysia have implemented Health, Safety and Environment Management System in the company which aim to guide and improve the overall Health, Safety and Environment culture in the organization. However, it seems like the implementation of Health, Safety and Environment has reach a plateau where incidents still happened despite the countless Health, Safety and Environment related initiatives conducted in the company. Hundreds of researches was done and models are proposed to measure the Health, Safety and Environment culture level in the organization, but there are no one satisfy model that can be used to identify the areas for improvement and action plan. Therefore, the focus of this study is to identify the current Health, Safety and Environment culture level in most of the oil and gas organization in Malaysia where a survey research is conducted on workers who work in the oil and gas company. A measurement matrix which are able to examine the level of the Health, Safety and Environment culture based on the Health, Safety and Environment Management System (HSE MS) is generated. With the proposed measurement matrix on culture, organizations are able to identify both the overall culture level and the specific areas that required improvement. Strategic plan can be assigned to these areas to achieve a mature Health, Safety and Environment culture in the oil and gas organization.